A 3D printed hydrogel to promote human keratinocytes spheroid-based growth - Tânia Margarida Couto Rocha (2022)
Tissue engineering uses cells and biomaterials to develop bioartificial tissue substitutes for different purposes. Although several skin models have been developed for pharmaceutical and cosmetic research, but also for skin wound healing, there are few studies on 3D cultures of keratinocytes in 3D printed scaffolds. So, the aim of this work was to develop a 3D-printed hydrogel scaffold able to promote human keratinocytes growth. Mesh 3D scaffolds were printed using an extrusion-based method with a 20% gelatin/ 5% alginate hydrogel where HaCaT cells were cultured for 7 days. Scaffolds kept their structure over one week and their stiffness only decreased after 7 days, showing good mechanical and structural characteristics, along with good biodegradability (27% weight lost). Viable keratinocytes (MTT assay) aggregated into spheroids, which is a 3D model capable of mimicking in vivo cells properties and phenotypes. Spheroids were formed on 47% of scaffolds pores and got larger over time, showing promising cell proliferation. F-actin staining showed cells irregular and interconnected shapes and organization over time. This method offers an easy and inexpensive solution for keratinocyte spheroid formation, which may be useful for tissue engineering as a cell delivery system, for pharmacological or basic research, or wound healing medical applications.